Mental disorders in the Black population: a scoping review - Rondinelli Salvador Silva; Yasmim Souza Rodrigues; Eduardo Sodré de Souza; Bruno Pereira da Silva; Luanda Ferreira Dias de Souza; Igor Hagedorn Reis; Ana Paula de Morais e Oliveira; Deivison Faustino Mendes; Patricia Lima Ferreira Santa Rosa (Frontiers in Public Health, 2026)
Introduction Mental disorders, psychiatric diagnosis, DSM/ICD classification, and mental health care represent major sources of global morbidity shaped by biological processes, social stressors, structural racism, inequities, and access barriers. In the Black population, racism, discrimination, social exclusion, and institutional bias may affect recognition, diagnosis, treatment, prognosis, and psychiatric outcomes. This scoping review aimed to map and summarize the available evidence on mental disorders in the Black population worldwide, highlighting how psychiatric knowledge and mental health care are shaped by racialized social structures. Methods The review was conducted according to JBI methodology and reported in accordance with the Preferred Reporting Items for Systematic Reviews extension for Scoping Reviews (PRISMA-ScR). Searches were conducted in MEDLINE, CINAHL, APA PsycINFO, Scopus, Embase, PubMed Central, Web of Science, the Virtual Health Library, the Brazilian Digital Library of Theses and Dissertations, and ProQuest Theses, with no restrictions on language or publication date. Sources addressing the Black population and mental disorders defined by diagnostic classification systems were included, covering manifestations, diagnoses, associated factors, access to care, interventions, barriers, and psychosocial consequences. Data were extracted using a purpose-built instrument and synthesized through thematic analysis, narrative synthesis, tables, and figures. Results A total of 2,131 records were identified; after screening, search updating, and full-text assessment, 254 sources were included. Because 89.0% of included sources originated in the United States, the findings have limited transferability across diverse Black populations and healthcare contexts worldwide. Most sources examined clinical, hospital, outpatient, or healthcare settings, indicating that the mapped evidence primarily reflects formal care environments rather than community contexts. The most frequent disorders were depressive disorders, substance use disorders, psychosis or schizophrenia, anxiety, bipolar disorder, neurodevelopmental or conduct disorders, trauma, suicidality, and eating disorders. The main barriers and associated factors included gender, access to services, socioeconomic determinants, violence, trauma, racism, discrimination, and stigma. Conclusion The evidence remains geographically concentrated and predominantly clinical-diagnostic, with limited transferability beyond the populations, services, classification systems, and contexts represented in included sources. These findings identify priorities for culturally responsive, antiracist, and equity-oriented research, but do not establish the effectiveness of specific policies, practices, or interventions. Systematic review registration OSF registration doi: 10.17605/OSF.IO/WQAVD .